2022
DOI: 10.1021/acscatal.1c05820
|View full text |Cite
|
Sign up to set email alerts
|

Coadsorption of NRR and HER Intermediates Determines the Performance of Ru-N4 toward Electrocatalytic N2 Reduction

Abstract: Electrochemical N 2 reduction (NRR) to ammonia is seriously limited by the competing hydrogen evolution reaction (HER), but atomic-scale factors controlling HER/NRR competition are unknown. Herein we unveil the mechanism, thermodynamics, and kinetics determining the HER/NRR efficiency on the state-of-the-art NRR electrocatalyst, Ru-N 4 , using grand canonical ensemble density functional theory (GCE-DFT). We show that NRR/HER intermediates coadsorb on the catalyst where NRR intermediates suppress HER and select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(80 citation statements)
references
References 68 publications
2
78
0
Order By: Relevance
“…This is incredibly difficult given that the binding energies of the reaction intermediates are intrinsically coupled, a correlation that is referred to as scaling relation [20] . Skulason and coworkers were the first to demonstrate that the occurrence of scaling relations limit the performance of NRR electrocatalysts for ammonia formation, [21] and, regrettably, scaling relations are present in any material class, ranging from metals to transition‐metal oxides (TMOs) or carbon‐based materials [21–25] . Given that TMOs are considered as HER‐inactive materials because they are not in favor of binding hydrogen, these materials are promising to achieve high Faradaic efficiency toward the NRR, [26,27] and this is the reason why in the present work TMOs are used as a prime example to derive general trends for the NRR.…”
Section: Introductionmentioning
confidence: 99%
“…This is incredibly difficult given that the binding energies of the reaction intermediates are intrinsically coupled, a correlation that is referred to as scaling relation [20] . Skulason and coworkers were the first to demonstrate that the occurrence of scaling relations limit the performance of NRR electrocatalysts for ammonia formation, [21] and, regrettably, scaling relations are present in any material class, ranging from metals to transition‐metal oxides (TMOs) or carbon‐based materials [21–25] . Given that TMOs are considered as HER‐inactive materials because they are not in favor of binding hydrogen, these materials are promising to achieve high Faradaic efficiency toward the NRR, [26,27] and this is the reason why in the present work TMOs are used as a prime example to derive general trends for the NRR.…”
Section: Introductionmentioning
confidence: 99%
“…Taking the surface Pourbaix diagram into consideration, DPD MoMo–py has a wide potential range (−0.94 to −0.06 V) to adsorb *N 2 without being competed by *H adsorption, and at this potential range, it offers superior NRR activity with a potential of −0.19 V. These findings might benefit the way for diporphyrins to be employed as inspiration for the design and discovery of selective and active NRR electrocatalysts. Future work exploring the explicit dependence of pH and applied potential for the reaction via grand canonical DFT can be done to achieve a more detailed understanding of NRR.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we employed the state-of-the-art constant potential, GCE-DFT methods to gain atomic understanding of N 2 RR performance on the 2D Ru-N 4 catalyst. [78] It has shown that the N 2 RR/HER competition cannot be understood without using GCE-DFT to address the potential-dependency in thermodynamics, kinetics, and charge transfer. Results from the GCE-DFT method indicate that the selective control over the N 2 RR chemistry can be achieved by limiting proton donors which are spatially separated from the Ru-N 4 active site.…”
Section: Advanced Theoretical Simulationmentioning
confidence: 99%